2018
DOI: 10.5114/ceji.2018.74874
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon alpha 2b in rheumatoid arthritis: good antigen for rheumatoid arthritis antibodies

Abstract: Aim of the studyInterferon alpha-induced arthritis and activation of the type 1 interferon pathway during rheumatoid arthritis (RA) has been well documented but the underlying mechanism remains unclear. This study addressed the binding specificity of antibodies with recombinant interferon alpha 2b (rIFN α-2b) in sera from different RA patients. Utilization of anti-hrIFN α-2b antibodies as a probe for estimation of interferon α-2b concentration in RA patients’ synovial fluid (SF) was also investigated.Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…According to the existing theories and our analysis, the possible mechanism of the susceptibility to DLBCL in RA patients is that LGALS2 causes persistent chronic inflammation and excessive activation of B cells through the production of many inflammatory factors and autoantibodies, thus leading to the occurrence of DLBCL (7), which also supported by previous studies reporting a strong relationship between lymphoma incidence and RA disease severity (43, 44). More importantly, type I IFN is not only one of the molecules involved in RA (45), but also an effective therapeutic target in DLBCL (46). In addition, we also observed the effect of LGALS2 on other immune cells and the relationship with immune checkpoints, the results of which indicated that LGALS2 has a significant regulatory effect on human immune response.…”
Section: Discussionmentioning
confidence: 53%
“…According to the existing theories and our analysis, the possible mechanism of the susceptibility to DLBCL in RA patients is that LGALS2 causes persistent chronic inflammation and excessive activation of B cells through the production of many inflammatory factors and autoantibodies, thus leading to the occurrence of DLBCL (7), which also supported by previous studies reporting a strong relationship between lymphoma incidence and RA disease severity (43, 44). More importantly, type I IFN is not only one of the molecules involved in RA (45), but also an effective therapeutic target in DLBCL (46). In addition, we also observed the effect of LGALS2 on other immune cells and the relationship with immune checkpoints, the results of which indicated that LGALS2 has a significant regulatory effect on human immune response.…”
Section: Discussionmentioning
confidence: 53%
“…IL-4, IL-13, and IL-10 all drive monocytes to M2 macrophages [ 35 ]; thus, the complex pro and antiosteoclastogenic effects drive the differentiation and activity simultaneously. Interestingly, earlier studies have shown increased concentrations of also other osteoclastogenesis-inhibiting factors, INF- α , IL-3, IL-27, and IL-33 in RA patient samples [ 36 – 39 ]. Together, these findings could explain some of the differences in RA and OA bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites lead to the generation of ROS that can damaged DNA and make DNA adducts [49]. Once DNA get damaged it alters its antigenicity leading to the generation of autoanti- bodies in autoimmune diseases [15][16][17][18][19][20][21][22][23][24][25][26]44]. P450-mediated hydroxylation also produced 16α-hydroxyestrone metabolites that exert its effect through binding to its receptor [51].…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that 16α-hydroxyestrone is responsible for causing breast cancer [15]. Infect, these estrogen metabolites play an important role in cancer as well as in autoimmune diseases [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%